Investigation of interactions between scales of motion in the stable boundary layer. (10th June 2016) - Vercauteren, Nikki; Mahrt, Larry; Klein, Rupert
Abstract : Interactions between motions on different time‐scales are investigated in the SnoHATS dataset of near‐surface stable boundary layer (SBL) turbulence. In an earlier study, the authors applied a data‐clustering methodology based on a bounded variation, finite element, vector autoregressive factor method (FEM‐BV‐VARX) to characterize the influence of non‐turbulent, submesoscale motions on the turbulence in the SnoHATS dataset. Regimes were identified, two of them weakly stable and two very stable turbulence states. In each identified regime, the variability of turbulent momentum fluxes is characterized here using an extended multiresolution flux decomposition methodology. The transport properties in each regime of near‐surface SBL turbulence are thereby assessed. The same methodology is used to investigate the scales of motion responsible for shear generation of turbulence.